Sosialisasi tentang Pencegahan Kenakalan Remaja dan Pemanfaatan Teknologi Secara Positif - Nofan, Nofansyah; Mardiansyah; Yoseph Herman Pasaribu (LPPM UNINUS, 2025)
The socialization program on preventing juvenile delinquency and promoting positive use of technology is a community service initiative aimed at providing education to students of MTs Al-Ikhlas Nipah Nipah regarding the negative impacts of juvenile delinquency and the importance of utilizing technology positively in daily life. The method applied in this program includes education through interactive discussions, material presentations, and practical activities on the wise use of technology. The results indicate an increase in students’ knowledge about the dangers of juvenile delinquency as well as a growing awareness to use technology as a tool for learning, creativity, and self-development. This program is expected to enhance the awareness of MTs Al-Ikhlas Nipah Nipah students in preventing juvenile delinquency while simultaneously optimizing the role of technology for positive purposes. Keywords: Juvenile Delinquency, Positive Technology, Education